La opción corporativista en Argentina y Chile: agrupaciones políticas y círculos intelectuales (1930-1970) - Gabriela Gomes (Les Cahiers ALHIM)
This paper intends to review the nationalist, fascist and catholic groups in favor of the corporatist doctrine in its state and anti-state version in Argentina and Chile between 1930 and 1970. At the end of World War II corporatism was discredited, however did not disappear from the political scene, but it adapted to different contexts and lasted for a long time. Our hypothesis is that survival because by 1950, it ceased to be an exclusive partner of nationalism and was incorporated by other political traditions.